SEED PRIMING OF WHEAT THROUGH SALICYLIC ACID TO INDUCE SALT STRESS TOLERANCE - Idrees, H; Shabbir, I; Khurshid, H; Khurshid, A; Tahira, RI; Fatima, F; Younas, A; Abbas, HG (Biological and Clinical Sciences Research Journal, 2022)
Wheat is an important cereal crop consumed throughout the world. Present study was planned to conduct in greenhouse of IMBB, University of the Lahore for determination of effects of salt stress on growth of wheat seedlings. Seed from selected wheat genotypes (SHAFAQ-2006, ANAJ-2017and Galaxy-2013) were used to grow in 54 pots, which were filled with 2kg pure washed sand. The sand was mixed with 500mg/kg of salt NaCl in each of the pot except of the control pots for wheat sowing. The seed of wheat variety were sown in triplicate pots with all irrigation requirements in equal manners. The use of salicylic acid (SA) for seed priming was more effective for number of roots per plant. The highest root length was recorded for treatment of SA priming + NaCl which indicated that the application of SA induced higher number of roots and long roots under salt stress conditions. The higher root water contents and shoot water contents were recorded under the application of water priming of seeds. The positive contribution of root water contents to root length indicated that the higher root water contents caused increase in shoot length due to higher water, mineral and nutrient absorption and retention which caused increase in photosynthetic rate and vice versa. It was found from results that the genotype GALAXY-2013 performed better under different treatments and SA priming application for root length, shoot length and number of roots per plant. The results suggested that the genotype GALAXY-2013 may be used to develop different wheat genotypes which may show higher grain yield under the applications of SA as seed priming compound while growing wheat in slat stress environment.